Impact of albumin on the survival of elderly patients with diffuse large B cell lymphoma - Beltran, Brady E. (2025)
Introduction: Diffuse large B cell lymphoma is the most common subtype of lymphoma. Albumin proves to be a prognostic factor in this subtype of lymphoma. Objective: The objective of this study is to evaluate the role of albumin in the survival of elderly patients with diffuse large B cell lymphoma  in a hospital in Peru. Material and methods: This was a retrospective study of 62 patients with diffuse large B cell lymphoma aged 80 or older. Results: In the multivariate analysis, bulky disease (HR= 3.1, 95% 1.5-6.4; p=0.003) and albumin (HR 3.8, 95% 1.9-7.6; p=0.001) were factors associated with survival. Conclusions: bulky disease and albumin were factors associated with overall survival in patients with diffuse large B cell lymphoma aged 80 or older.